Efficacy and safety of daily home-based transcranial direct current stimulation as adjunct treatment for bipolar depressive episodes: Double-blind sham-controlled randomized clinical trial - Lee, Jangwon; Lee, Chan Woo; Jang, Yoonjeong; You, Ji Seon; Park, Yun Seong; Ji, Eunjeong; Yu, Hyeona; Oh, Sunghee; Ryoo, Hyun A.; Cho, Nayoung; Park, Ji Yoon; Yoon, Joohyun; et al. (Frontiers in Psychiatry, 2022)
Background: Although transcranial direct current stimulation (tDCS) is known to be a promising therapeutic modality for unipolar depression, the efficacy and safety of tDCS for bipolar depressive episodes are still unknown and clinical trials of home-based tDCS treatment are scarce. As a result, we set out to investigate the efficacy and safety of home-based tDCS for the treatment bipolar depressive episodes (BD). Methods: Participants (n=64), diagnosed as bipolar disorder (BP) as per the diagnostic and statistical manual of mental disorders (DSM-5), were randomly assigned to receive tDCS. Hamilton Depression Rating Scale (HDRS-17) scores were measured at the baseline, week 2, 4, and 6, and home-based tDCS (for 30 minutes with 2 mA) was self-administered daily. Results: Of the 64 patients (15.6% BP I, 84.4% BP II), 41 patients completed the entire assessment. In the intention-to-treat analysis, time-group interaction for the HDRS-17 (F3,146.36 = 2.060; p = 0.108) and adverse effect differences between two groups were not statistically significant, except the pain score, which was higher in the active group than the sham group (week 0–2: p < 0.01, week 2–4: p < 0.05, and week 4–6: p < 0.01). Conclusion: Even though we found no evidence for the efficacy of home-based tDCS for patienst with BP, this tool was found to be a safe and tolerable treatment modality for bipolar depressive episodes.